2004
DOI: 10.1017/s0001924000000142
|View full text |Cite
|
Sign up to set email alerts
|

Heliplat®: high altitude very-long endurance solar powered UAV for telecommunication and Earth observation applications

Abstract: Research is at present being carried out at the Turin Polytechnic University with the aim of designing an HAVE/UAV (high altitude very-long endurance/unmanned air vehicle). The vehicle should climb to 17-20km by mainly taking advantage of direct Sun radiation and thereafter maintain a level flight; during the night, a fuel cells energy storage system would be used. A computer program has been developed to carry out a parametric study for the platform design. The solar radiation change over one year, the altitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 4 publications
0
37
0
Order By: Relevance
“…The BWB solution, compared to the conventional design [6][7][8][9][10][11][12] [6][7][8], has been used for the preliminary design of SHAMPO. Propeller characteristics are obtained using two in-house FORTRAN developed tools.…”
Section: Internal and External Layoutmentioning
confidence: 99%
See 1 more Smart Citation
“…The BWB solution, compared to the conventional design [6][7][8][9][10][11][12] [6][7][8], has been used for the preliminary design of SHAMPO. Propeller characteristics are obtained using two in-house FORTRAN developed tools.…”
Section: Internal and External Layoutmentioning
confidence: 99%
“…The Department of Aerospace Engineering at the Politecnico di Torino (POLITO/DIASP, Scientific Responsible Prof. Romeo) has acquired a great deal of experience, starting from 1994, in the design of solar-powered UAV as high altitude very long endurance platform positioned in the stratosphere at an altitude of 17-20 km and with an endurance of about four months [6][7][8][9][10][11][12][13][14]. Started under a grant from the Italian Space Agency (ASI), a great amount of work was carried out within two European funded projects (HeliPlat w and Capecon) whose final task was to fill the European gap in knowledge and feasibility of such kinds of innovative systems.…”
Section: Introductionmentioning
confidence: 99%
“…They are considered as a valuable and ubiquitous technology in many applications such as mapping, topography, telecommunications, surveillance, and agricultural management [2][3][4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…The first one is the near-space platform techniques, the other is the operation mode design and the corresponding imaging scheme. For the first problem, as the potential value of the near space becomes more and more clear, many studies related to the near-space platform have been reported [11,12,13,14,15,16,17]. Near-space platforms can be clarified into three types: near-space airship (NSA), near-space long-endurance low-speed-maneuvering vehicle (NLLV) and near-space short-endurance high-speed-maneuvering vehicle (NSHV), as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%